Sustainable Design and Manufacturing 2020 : Proceedings of the 7th International Conference on Sustainable Design and Manufacturing (KES-SDM 2020) /: Proceedings of the 7th International Conference on Sustainable Design and Manufacturing (KES-SDM 2020). (2020) - Unknown
No abstract available